'We don't do that': A constructivist perspective on the use and non-use of private military contractors by Denmark. (March 2019) - van Meegdenburg, Hilde
In this article I put forward a social constructivist perspective on state use of Private Military and Security Contractors (PMSCs). I will argue that state outsourcing decisions are, to a large extent, shaped by nationally shared values, understandings and dispositions. Concretely, I first provide a detailed overview of the extent of domestic and deployed contracting by the Danish Defence and, thereafter, based on a number of semi-structured interviews, I expose the dominant understandings that shaped how PMSCs have come to be understood in Denmark. By so doing I can show that the employment of PMSCs by the Danish Defence remains comparatively limited because it is largely perceived as inappropriate and as incompatible with what it means to be 'Danish'. Although Denmark too has to balance its international engagements with the limited resources allocated to defence (the typical functional pressures) Danish particular 'soft' neoliberalism and 'hard' commitments to IHL speak against using private actors to make that possible. This means I take in the more abstract, macro-level discussions on the end of the Cold War and the advent of neoliberalism but go beyond by asking whether, and if so how, these and other collective experiences and understandings actually (co-)shape(d) outsourcing decisions.